Planning for the Laobaixing : Public Participation in Urban Transport Project, Liaoning, China - Chen, Wenling; Mehndiratta, Shomik Raj (World Bank, Washington, DC, 2014)
International experience suggests that in the realm of urban transport, a public participation process can be a valuable complement to the technical planning process in generating good projects with widespread distributional benefits that minimize concentration of adverse impacts. If properly designed, participation processes also offer an opportunity to incorporate the interests of vulnerable groups into the planning process. This paper presents a recent case study of a World Bank financed urban infrastructure improvement project in Liaoning, China, where the successful development of a meaningful public participation process influenced project design to better address the broad needs of the project beneficiaries. Particularly, the participatory process significantly influenced the project design and raised city leaders' sensitivity to public needs. Through the process the project shifted focus from major road expansion to secondary road improvements. Additionally, the participation processes picked up latent issues to better address needs of non-auto users, women and other urban vulnerable. The outcomes of the Liaoning participatory project indicate that a mainstreamed participatory process offers the potential to systematically reveal and address critical issues and public needs early in the planning process, which leads to higher value projects to accomplish investment goals.